CONCEPTUAL BASES FOR CREATING FREE ECONOMIC ZONES IN UZBEKISTAN - Dilmonov K. B. (Galaxy International Interdisciplinary Research Journal, 2022)
The article analyzes free economic zones, their essence, the legal basis for their organization, specific ways to create free economic zones in the region.